Features of Creativity and Conceptual Thinking of Students Studying in the Direction of "Software Engineering "(Engineers-Kognitologs) - Ivakhnenko O.N; Smolyaninova V.A (Moscow State University of Psychology and Education, 2018)
The article presents the features of creativity of students studying in the direction of "Software engineering". The necessity to study the features of the creativity of students of cognitive engineers for their future professional activities in the modern world determines the problem of research. The hypothesis of the study is that the creativity of students studying in the direction of "Software engineering", and students studying studying in the direction of "Management", as well as students studying in the direction of "Software engineering", boys and girls will have their own features. The sampling consisted of students of the 4th year (N=100): studying in the MIT in the direction of "Software engineering" (engineers-kognitologs (N=50)), and students in the MGIU in the direction of "Management" (N=50), (students managers). To determine the level of creativity was used: the test of P. Torrens "Doodle", "Circles", "Supply", the test "Creativity" of N.F. Vishnjakova. The differences between the level of creativity in groups of girls and boys, students of managers and students engineers-kognitologs are detected. By the sum of the criteria, students managers have a higher level of performance than a group of students of engineers-kognitologs, and girls engineers-kognitologs showed a higher level of creativity than boys. The system of exercises for the development of creativity and conceptual thinking using the means of acting is described.